Pharmaceutical patents: reconciling the human right to health with the incentive to invent. Issue 7 (July 2020) - Khachigian, Levon M.
Highlights: Drug discovery is exciting and transformative but conflicts exist between the incentive to invent and the rights of others to access medicines Tensions between fundamental rights to access essential medicines and rights of the inventor and investors are considered Effective incentives to innovate in developed countries can lead to global improvements in access to medicine if the intellectual property system is calibrated to permit this Compulsory licensing and alternative mechanisms facilitating global access to drugs in the context of rights to the highest attainable standard of health and intellectual property are also discussed Abstract : In developed countries that protect core aspects of the fundamental human right to the highest attainable standard of health, how does that right intersect with intellectual property rights? Here, the human rights implication of providing access to all cancer drugs recommended by experts in a developed country is considered in the context of conflict between the incentive to invent and the rights of others to access medicines. Effective incentives to innovate in developed countries can lead to global improvements in access to medicine if the intellectual property system is calibrated to permit this. This depends partly on the usefulness of compulsory licensing and alternative mechanisms facilitating global access to drugs. This review considers tensions between fundamental rights to access essential medicines and rights of the inventor and investors, including the pharmaceutical industry.